Supersivion Program in Improving Teachers Profesional Competence at SD Negeri 5 Juli, Bireun Regency - Yusnidar, Yusnidar; Murniati, Murniati; Khairuddin, Khairuddin (FKIP Universitas Lampung, 2021)
The aim of the study was to determine the supervisory program, implementation of supervision to improve the professional ability of teachers in the SD Negeri 5 Juli in Bireun district. This study uses a descriptive method with a qualitative approach. Data collection was carried out by observations, interviews, and documentation. The subject of this study is the supervisor, principal, head of the teacher’s work team, and senior teacher. Data collection techniques through: observation, interviews and documentation studies. Data analysis was carried out by using data reduction, data presentation and withdrawal of conclusions. The results of the study show: (1) The supervisory program consists of annual plans and semesters. (2) Surveillance has been running with efforts to improve teacher competence professionally. Such supervision programs include classroom supervision, class observations, Improwage quizzes, case documentation, interviews, questionnaires, and written reports; (3) The obstacles faced in supervision are the absence of coordination between the supervisor and the principal and teacher on the schedule of the meeting. Keywords: supervision implementation, supervisors, profesional teachers DOI: 10.23960/jpp.v11.i2.202127